(untitled) (Journal of Industrial and Mechanical Engineering, 2021)
The current social and economic scenario has increasingly demanded that industries adopt a vision focused on the responsible use of resources and environmental preservation. These factors, added to the search for competitiveness and the reduction of operating costs (such as equipment wear due to fatigue), have favored an increase in studies aimed at industrial energy efficiency. In the last five years, a significant number of studies have been published that combine energy efficiency with multi-criteria decision-making, contributing to the evolution of knowledge. This article presents a bibliometric analysis on the subject to identify the evolution of this topic, verifying the most cited works, the methods applied, the industrial areas studied, and the contributions and future suggestions identified.